1999
DOI: 10.1002/hep.510300119
|View full text |Cite
|
Sign up to set email alerts
|

The pravastatin-induced decrease of biliary cholesterol secretion is not directly related to an inhibition of cholesterol synthesis in humans

Abstract: 3-Hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors have been reported to suppress biliary cholesterol secretion and saturation. It remains unproven whether this is mediated by inhibition of cholesterol synthesis. Therefore, the effect of a long-term administration of pravastatin on cholesterogenesis and on biliary lipid secretion was investigated in seven healthy volunteers. Placebo or 40 mg of pravastatin were taken daily at bedtime for 5 weeks using a double-blind crossover design. During t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…Most recently, Schonewille et al have reported that rosuvastatin, atorvastatin and lovastatin enhance the biliary cholesterol secretion 51 . In contrast, pravastatin induces a decrease in the biliary cholesterol secretion in healthy volunteers 52 . Bile containing normal levels of bile salts, PC and cholesterol does not lead to hepatocellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Schonewille et al have reported that rosuvastatin, atorvastatin and lovastatin enhance the biliary cholesterol secretion 51 . In contrast, pravastatin induces a decrease in the biliary cholesterol secretion in healthy volunteers 52 . Bile containing normal levels of bile salts, PC and cholesterol does not lead to hepatocellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in line with data reported previously, we found increased biliary cholesterol secretion in statintreated mice. However, a reduction of biliary cholesterol secretion and saturation index has been observed in humans treated with pravastatin (17,24) or lovastatin (54). In addition, statin use was associated with a reduction in the risk of gallstone disease (55), supporting decreased rather than increased biliary cholesterol secretion rates.…”
Section: Discussionmentioning
confidence: 99%
“…The effects on biliary secretion may indicate inhibition of hepatic cholesterol synthesis in humans. However, the few early studies in statin-treated humans that applied direct methods to measure cholesterol synthesis and failed to prove a reduced cholesterol synthesis (16) or even pointed toward increased cholesterol synthesis (17) indicate that whole body cholesterol synthesis may also be augmented in humans. If increased cholesterol synthesis after statin treatment is also the case in humans, then it would be important to investigate whether this would also lead to enhanced fecal excretion of neutral sterols or if the newly synthesized cholesterol undergoes a different fate.…”
Section: Discussionmentioning
confidence: 99%
“…Statins can reduce hepatic cholesterol biosynthesis and thereby decrease biliary cholesterol secretion [11]. Animal studies have indicated that statins can prevent the gallstone formation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%